Analisis Faktor -Faktor Yang Mempengaruhi Kepuasan Konsumen Abuteke Barbershop Di Kota Pacitan - Yahya, Fajar Nur Budy; Handayani, Rini; Marsudi, Hidup (Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital, Ekonomi Kreatif, Entrepreneur (JEBDEKER), 2023)
The purpose of this study is to investigate the impact of service quality, facilities, promotions, and prices on customer satisfaction at Abuteke Barbershop in Pacitan, which is located at Jalan. Hos cokroaminoto No. 10 Pacitan. This type of research is explanatory research and uses data collection techniques through the distribution of questionnaires and interviews from October 2022 to November 2022, using a sample of 100 respondents. While the data analysis method used includes descriptive statistical tests, research instrument tests consisting of validity tests, reliability tests, classical assumption tests, and multiple linear regression tests The results of this study show that using the t test, the four variables of service quality, facilities, promotions, and prices have a positive effect on consumer satisfaction, whereas using the F test, the four variables affect customer satisfaction simultaneously. The adjusted R squared figure is 0.614, or 61.4%. Based on the results of this study, variable service quality has an effect on customer satisfaction; promotion has an effect on customer satisfaction; facilities have an effect on customer satisfaction; and prices have an effect on consumer satisfaction